Economic planning and development of North-Eastern states - Banerjee, Amalesh; Kar, Biman (New Delhi Kanishka, 1999)
This book deals with the Economy of the North-Eastern States which have enormous wealth endowment and need careful attention for appropriate strategy for development. The Volume focusses attention on the existing stock of situation of the states, the prod
Keywords: Economic development; Economic policy; Central policy; Agriculture-Economic aspects